Proposing a Parkinson's disease–specific tremor scale from the MDS‐UPDRS. Issue 8 (11th June 2015) - Forjaz, Maria João; Ayala, Alba; Testa, Claudia M.; Bain, Peter G.; Elble, Rodger; Haubenberger, Dietrich; Rodriguez‐Blazquez, Carmen; Deuschl, Günther; Martinez‐Martin, Pablo; for the International Parkinson and Movement Disorder Society Tremor Rating Scale Task Force
ABSTRACT Background This article proposes an International Parkinson and Movement Disorder Society (MDS)‐UPDRS tremor‐based scale and describes its measurement properties, with a view to developing an improved scale for assessing tremor in Parkinson's disease (PD). Methods This was a cross‐sectional, multicenter study of 435 PD patients. Rasch analysis was performed on the 11 MDS‐UPDRS tremor items. Construct validity, precision, and test‐retest reliability were also analyzed. Results After some modifications, which included removal of an item owing to redundancy, the obtained MDS‐UPDRS tremor scale showed moderate reliability, unidimensionality, absence of differential item functioning, satisfactory convergent validity with medication, and better precision than the raw sum score. However, the scale displayed a floor effect and a need for more items measuring lower levels of tremor. Conclusions The MDS‐UPDRS tremor scale provides linear scores that can be used to assess tremor in PD in a valid, reliable way. The scale might benefit from modifications and studies that analyze its responsiveness. © 2015 International Parkinson and Movement Disorder Society